2018
DOI: 10.1063/1.5011693
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved optical absorption microspectroscopy of magnetic field sensitive flavin photochemistry

Abstract: The photochemical reactions of blue-light receptor proteins have received much attention due to their very important biological functions. In addition, there is also growing evidence that the one particular class of such proteins, the cryptochromes, may be associated with not only a biological photo-response but also a magneto-response, which may be responsible for the mechanism by which many animals can respond to the weak geomagnetic field. Therefore, there is an important scientific question over whether it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…In recent years, to address this problem and to directly investigate MFEs of RPs in biological systems, some research groups, including ours, have developed a number of microscope-based imaging approaches [transient absorption (TA) based (15,16) and fluorescence based (17)]. Some of our recent experiments have demonstrated that the photochemistry of FAD in aqueous solution is magnetic field sensitive, even at physiological pH, using our TA-based microscope (18).…”
mentioning
confidence: 99%
“…In recent years, to address this problem and to directly investigate MFEs of RPs in biological systems, some research groups, including ours, have developed a number of microscope-based imaging approaches [transient absorption (TA) based (15,16) and fluorescence based (17)]. Some of our recent experiments have demonstrated that the photochemistry of FAD in aqueous solution is magnetic field sensitive, even at physiological pH, using our TA-based microscope (18).…”
mentioning
confidence: 99%
“…20 There are other, related, techniques which make use of the field-modulation and derivative detection. In recent years, field-modulation technique has been combined with laser scanning to yield both fluorescence 21 and absorptionbased ModMARY imaging 22,23 (referred to as magnetofluorescence imaging (MFI) and magnetic intensity modulation (MIM) imaging respectively). The general technique of stimulus-modulation can be seen in many fields of spectroscopy, most notably optical spectroscopy, for example in frequency (wavelength) modulation using tunable light sources, cavity spectroscopy and electron paramagnetic resonance (EPR).…”
Section: Introductionmentioning
confidence: 99%
“…20 There are other, related, techniques which make use of the field-modulation and derivative detection. In recent years, field-modulation technique has been combined with laser scanning to yield both fluorescence 21 and absorptionbased ModMARY imaging 22,23 (referred to as magnetofluorescence imaging (MFI) and magnetic intensity modulation (MIM) imaging respectively). The general technique of stimulus-modulation can be seen in many fields of spectroscopy, most notably optical spectroscopy, for example in frequency (wavelength) modulation using tunable light sources, cavity spectroscopy and electron paramagnetic resonance (EPR).…”
Section: Introductionmentioning
confidence: 99%